(untitled) (قضايا سياسية, 2025)
This study deals with the Russian-Georgian war that broke out on 8/8/2008 as one of the evidences through which Russia's move to restore its former influence can be understood; as that war represented a great opportunity for Moscow to achieve its interests through a crisis management strategy to restore its influence in Georgia on the one hand and to send a message to the West and the former Soviet states trying to get out of the Soviet sphere of influence that it is capable of protecting its interests and influence and dealing with it as a major state with an effective and influential role. Likewise, the United States adopted a crisis management strategy with Russia in order to achieve its interests in the region with Georgia and the European Union, in addition to the fact that the future of the Russian strategy towards Georgia does not go beyond the framework of Russia's quest to dominate it in a way that ensures that it does not become a pivot point for the West and NATO in the Caucasus region.